Self-Efficacy as a Mediator of Leadership, Learning Organization, Motivation, and Teachers’ Innovative Behavior - Fenti Farleni; Syadeli Hanafi; Dase Erwin Juansah (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study examines the uneven development of innovative behavior among public elementary school teachers in responding to changing learning demands. It aims to analyze the direct effects of transformational leadership, learning organization, motivation, and self-efficacy on teachers’ innovative behavior and to test the mediating role of self-efficacy. A quantitative explanatory design was employed. Data were collected through a closed-ended Likert-scale questionnaire administered to 374 public elementary school teachers in Serang Regency, selected through proportional stratified sampling from a population of 5,645 teachers. Hypotheses were tested using Structural Equation Modeling based on Partial Least Squares. The findings show that transformational leadership, learning organization, motivation, and self-efficacy positively affect teachers’ innovative behavior. The three exogenous variables also positively influence self-efficacy. Self-efficacy emerged as the strongest predictor and partially mediated all indirect relationships. These results contribute to educational management by emphasizing the importance of strengthening teachers’ professional confidence in developing school innovation.